Word and image : Patrick Cullinan and Judith Mason's Selected Poems 1961-1994 : a case for the special edition artist's book - Commin, Jane (Department of English Language and Literature, 2024)
[PAGE 1-3 missing] This dissertation argues for the past and continuing importance of the special edition book. Focusing in particular on one instance of books/artworks of this sort, the writer, Jane Elizabeth Commin, presents several arguments in order to underline her thesis. tn the ï¬ rst place she looks at the history of the institution of the artistâ€™s book and livre dâ€™artiste. Reviewing the history of such a book, she relates the artist's book to the history of aestheticism as a 19th century artistic and literary movement, and proceeds to show the artistâ€™s book is an extreme exempliï¬ cation of the principle of beauty central to the artistic movement. In the second chapter she focuses on a collaboration between the English-language South African poet Patrick Cullinan and the equally well-known South African artist Judith Mason. Drawing on interviews with both collaborators conducted by the writer, the dissertation outlines both the artist and writer's perceptions as to their practise and the nature of the collaboration itself. This chapter is then followed by theoretical excursus in which the theories of the French semiotician Claude Gandelman are outlined in their relevance to the reading of the word/image nexus discussed. In particular, the haptic/optic division Gandelman theorises is shown to be particularly useful in accounting for the unique aesthetic experience generated by special edition books in general. In the central chapter of the thesis, these relations are demonstrated through a close reading of the way in which the image works with the text and the text with the image in the speciï¬ c instance of the 1992 special edition of Patrick Cullinanâ€™s Selected Poems I 96!-1994 (Johannesburg: The Artistâ€™s Press). ' The thesis comes to the conclusion that, while the special edition or artistâ€™s book is an elite form of artmaking, it nevertheless embodies values which go to the heart of the artistic and literary experience and therefore is in fact a defence of the artistic experience itselfâ€˜. To support her argument the writer has drawn from interviews she conducted with South African artists and writers, including: Patrick Cullinan, Judith Mason, Pippa Skotnes, Vivian van der Merwe, Fiona Moodie, Lyn Smuts and Gregory Kerr. These interviews are included in addenda at the end of the dissertation. The writer also draws from the work of literary and art critics and theorists, including: R.V. Johnson, Johanna Drucker, Roger Kimball, Roland Barthes, Elaine Scarry, Claude Gandelman, Wendy Steiner, Octavio Paz and George Steiner.